(untitled) (Research, Society and Development, 2021)
This study aimed to understand and develop didactic strategies that enable teaching physics concepts in an engaging way and promote meaningful learning in the context of 1st year high school students during the Covid 19 pandemic period. The proposed methodology will aim at encourage students to actively learn, through the mediation of the teacher and the use of computer simulations, concepts of the physical discipline. Through these tools it will be possible to give students the opportunity to work with animations of virtual representations of phenomena. The “Forces and Motion” applet is relevant for understanding the physical concepts studied, as it allows the student to manipulate this applet and draw their own conclusions about the subject.